Expression of GPR109A in dairy cattle immune cells - Knight, Mylah L.; Mamedova, L.K.; Bradford, Barry J. (My University, 2019)
GPR109A is a Gi-coupled receptor for nicotinic acid (NA; niacin) as well as β-hydroxybutyrate (BHB). In cattle, NA is known to suppress the breakdown of adipose triglycerides, primarily by acting on the GPR109A receptor. Niacin binding activates the GPR109A receptor and leads to a decrease in cyclic AMP concentrations inside the cell. Dairy cows in early lactation have high concentrations of BHB, which may have important effects on immunity via GPR109A signaling. However, it remains unknown to what extent this receptor is expressed by key immune cells during this period of time. The objective of this study was to determine mRNA abundance and protein expression of GPR109A in immune cells of periparturient dairy cows. Heparinized blood (50 mL) was collected from 5 healthy Holstein cows and diluted with phosphate-buffered saline (PBS) at a 1:1 ratio. Ficoll was added to the samples and centrifuged to isolate immune cells. Pierce BCA Total Protein Assay Kit was used to determine the concentration of the total protein in isolated immune cell samples. 40 μg of protein sample were analyzed by Western Blot. The primary rabbit polyclonal antibody (HCAR2, ABClonal) was used at 1:500 and the secondary antibody (goat anti-Rabbit IgG, sc-2020; Santa Cruz Biotechnology) at 1:10000 to detect GPR109A protein expression. Quantitative real-time PCR was performed to determine mRNA abundance in immune cell samples. Relative mRNA abundance was quantified by the delta-Ct method with control genes RPS15 and GAPDH used to normalize values. GPR109A receptor mRNA and protein were found both key types of innate immune cells (monocytes and neutrophils) of dairy cattle throughout the transition to lactation, with no significant changes detected over time. Previously-reported associations between high blood BHB concentrations and poor immune function may be linked by GPR109A signaling.
Keywords: Spring 2019